Princípio da sadia qualidade de vida na perspectiva do saneamento básico como direito fundamental - Feijó, Nathalia Vargas (Universidade do Vale do Rio dos Sinos, 2021)
This final paper demonstrates the importance of environmental law in the society’s life, especially in an area that deserves a lot of attention and that has been discussed in international initiatives, legal norms, political debates, in other words, the efficiency of fundamental principles, such as the healthy quality of life and the effectiveness of essential services as basic sanitation. Well, water is the most precious good in all aspects of human life, but essentially to keep the individual's global well-being. There are a lot of attempts over the years to make access to sanitation effective and universal, besides using environmental resources in an effective and responsible way. Recently, with the advent of Law No. 14.026, which talks about the New Legal Framework for Basic Sanitation, which changed the Law No. 11.445 that was the current one by now, there was an update and changes in the normative treatment about the access to the potable water, in order to make the provision of this service more effective and to ensure its universalization, a bigger protection to the environment, care for natural resources and technology implementation. Basic sanitation is not limited only to access water and sewage treatment, but also to issues related to health and quality of human life, according to the article 225 of the federal Constitution, since there is no way disconnect a propitious and balanced environment with access to the rights and legal guarantees, with a healthy and quality human life.
Keywords: Direito ambiental; Saneamento básico; Sadia qualidade de vida; Água potável; Universalização; Recursos naturais; Environmental law; Basic sanitation; Healthy quality of life; Potable water; Universalization; Natural resources